Heuristic Retrospection of Meta-Architectural Constructs Within Sava Amphitheater Planning (Belgrade) - Ciganović, Aleksa S.; Stevanović, Vladimir M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
This paper is concerned with the observation of qualitative changes of planning solutions for the Sava Amphitheater in Belgrade in the latter half of the 20th century. The theoretical framework within which these changes are examined is Јеаn-Michel Berthelot’s epistemological program of thought, with its trifold polarity: naturalist, intentional, and symbolic. On the basis of critical analysis of the spatial synthesis in the planning solutions for the Sava Amphitheater, the paper hypothesizes that it is possible to identify chronologically the architectural planning and design solutions as evolving from radicalist to liberalist to conservativist thought, which may be taken to, analogously, correspond to the concept of transition from the naturalist to the intentional to the symbolic pole, as attributes of the contemporary epistemological program of thought of the second half of the 20th century. Following the transition of Berthelot’s epistemological poles from the standpoint of a general understanding of socio-cultural and socio-technical programmatic changes, this paper aims to establish the possibility of defining the notion of meta-architectural heritology as a constructionist modality of thought, which establishes certain rules of meta-architectural anthropology. The result of a transdisciplinary introduction into the investigative focus of a constructionist theoretical program points to the fact that every form of technical contemporaneity derives its value from mediated correspondences with heritage according to a model constructed by observation from the “outside,” from the field of historical spatial samples. The paper concludes that the constructionist transgression as a philosophical and socio-hu- manist dogma is an essential mechanism for finding criteria for the use of the two most widespread analytical architectural approaches—research by design and grounded theory approach.
Keywords: meta-architectural constructionism; architectural iconology; Јеаn-Michel Berthelot; Sava Amphitheater (Belgrade)